The Effect of Pain Catastrophizing on Endogenous Inhibition of Pain and Spinal Nociception in Native Americans: Results From the Oklahoma Study of Native American Pain Risk - Toledo, Tyler A (Ann Behav Med, 2020)
BACKGROUND: Conditioned pain modulation (CPM) is a task that involves measuring pain in response to a test stimulus before and during a painful conditioning stimulus (CS). The CS pain typically inhibits pain elicited by the test stimulus; thus, this task is used to assess endogenous pain inhibition. Moreover, less efficient CPM-related inhibition is associated with chronic pain risk. Pain catastrophizing is a cognitive-emotional process associated with negative pain sequelae, and some studies have found that catastrophizing reduces CPM efficiency. PURPOSE: The current study examined the relationship between catastrophizing (dispositional and situation specific) and CPM-related inhibition of pain and the nociceptive flexion reflex (NFR; a marker of spinal nociception) to determine whether the catastrophizing–CPM relationship might contribute to the higher risk of chronic pain in Native Americans (NAs). METHODS: CPM of pain and NFR was assessed in 124 NAs and 129 non-Hispanic Whites. Dispositional catastrophizing was assessed at the beginning of the test day, whereas situation-specific catastrophizing was assessed in response to the CS, as well as painful electric stimuli. RESULTS: Situation-specific, but not dispositional, catastrophizing led to less NFR inhibition but more pain inhibition. These effects were not moderated by race, but mediation analyses found that: (a) the NA race was associated with greater situation-specific catastrophizing, which led to less NFR inhibition and more pain inhibition, and (b) situation-specific catastrophizing was associated with greater CS pain, which led to more pain inhibition. CONCLUSIONS: Catastrophizing may contribute to NA pain risk by disrupting descending inhibition.